Avaliação da transmissão vertical e horizontal de Neospora caninum (Long, 1990) em bovinos de criação extensiva, cronicamente infectados, no Brasil - Cunha Filho, Nilton Azevedo da (2013)
Neospora caninum is causing great economic losses in cattle, due to abortion. It has been shown that the transmission of N. caninum is the primary route of infection in cattle, followed by horizontal transmission. Few studies demonstrate the outcome of this type of transmission in herd raised in pasture cattle. The first experiment aimed to evaluate the occurrence of vertical transmission of N. caninum in beef cattle and verify the relationship between seropositivity and abortion. Blood was collected from mothers in the pre-pregnancy and after, three more times in the gestation period, plus a sampling of calves at birth. The seroprevalence in the arrays found in the screening was 32.2% (29/90). The vertical transmission rate was 75.8% and all dams evaluated completed pregnancy, demonstrating that N. caninum is present on the property studied, with high transmission rates, but no apparent influence on the reproductive performance of dams. The second experiment aimed to demonstrate the importance of horizontal transmission in maintaining N. caninum in the same herd. Were accompanied by serological tests, 61 seronegative mothers during pregnancy thirds and their calves at birth (n = 61) and during the first year of life (n = 24). No seroconversion occurred in any of the dams. In calves, however, that seroconversion occurred, indicative of horizontal infection by N. caninum, 12.5% at the end of 12 months. This indicates that horizontal transmission interference occurred in this herd. The third experiment aimed to detect the presence of DNA of N. caninum in umbilical cord of calves positive of positive dams. Was collected the umbilical cord of 20 calves at birth for laboratory testing by PCR. The DNA of the parasite was confirmed by 1/20 (5.0%) umbilical cords. This is the first report of the detection of DNA from N. caninum in umbilical cord of calves by PCR.